Dynamic Change of Intestinal Duplication in an Adult Patient: A Case Report and Literature Review - Abhishek Shah; Jimin Du; Yutian Sun; Dianbo Cao (Case Reports in Medicine)
Intestinal duplication in an adult is an uncommon congenital abnormality because only minority of cases present in adulthood. More than 80% of cases occur before the age of two years as an acute abdomen, bowel obstruction or other complications associated with it. Duplication has two types, either cystic or tubular. Here, we report a case of an adult who was diagnosed preoperatively on CT scan as tubular intestinal duplication. CT images showed change in the morphology of the cystic mass after one week of antibiotics administration. On histopathological analysis, the resected duplicated segment had esophageal epithelium in addition to the intestinal gland. So far, we found no report describing CT findings of dynamic change of ileal duplication in the English literatures.